Black Soldier Fly Diet Impacts Soil Greenhouse Gas Emissions From Frass Applied as Fertilizer - Rummel, Pauline Sophie; Beule, Lukas; Hemkemeyer, Michael; Schwalb, Sanja Annabell; Wichern, Florian (Frontiers in Sustainable Food Systems, 2021)
Increased global production of animal-based protein results in high greenhouse gas (GHG) emissions and other adverse consequences for human and planetary health. Recently, commercial insect rearing has been claimed a more sustainable source of animal protein. However, this system also leaves residues called frass, which—depending on the insect diet—is rich in carbon (C) and nitrogen (N), and could thus be used as fertilizer in agriculture. The impact of this kind of fertilizer on soil GHG emissions is yet unknown. Therefore, we investigated the effect of black soldier fly (Hermetia illucens L.) frass derived from a carbohydrate (Carb-) or a protein (Prot-) based diet applied at two different application rates to an arable soil on C and N fluxes and microbial properties in a 40-day incubation experiment. CO2, N2O, NO, N2, CH4, water extractable organic C (WEOC), and inorganic N were continuously measured quantitatively. At the end of the incubation, microbial biomass (MB), stoichiometry, community composition, and abundance of functional genes were assessed. Along with a strong increase in WEOC and CO2, Carb-frass caused strong initial N2O emissions associated with high N and C availability. In contrast, Prot-frass showed lower CO2 emissions and N2O release, although soil nitrate levels were higher. At the end of incubation, MB was significantly increased, which was more pronounced following Carb-frass as compared to Prot-frass application, and at higher amendment rates. Fungal abundance increased most from both frass types with an even stronger response at higher application rates, whereas bacterial abundance rose following Carb-frass as compared to Prot-application. Abundance of functional genes related to ammonia-oxidizing bacteria and archaea were enhanced by high frass application but did not clearly differ between frass types. C use efficiency of microorganisms, as revealed by the metabolic quotient, was most strongly reduced in the high Prot-frass application rate. Overall, insect diet influenced available C and N in frass and thus affected mineralization dynamics, GHG emissions, and microbial growth. Overall, emissions were very high undermining the potential environmental benefit of insect based protein production and calling for more detailed analyses before frass is widely applied in agriculture.